THE LEVEL OF UNDERSTANDING OF THE YOUNG GENERATION ON THE CONCEPT AND DANGERS OF CORRUPTION BEFORE AND AFTER PARTICIPATING IN ANTI-CORRUPTION EDUCATION IN KLAMBIR LIMA KEBUN VILLAGE, HAMPARAN PERAK DISTRICT - Rahmayanti; Suci Ramadani; Nia Agustri Lase (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the level of understanding of the younger generation on the concept and dangers of corruption before and after participating in anti-corruption education in Klambir Lima Kebun Village, Hamparan Perak District. Anti-corruption education is expected to increase public understanding and awareness, especially the younger generation, about the negative impact of corruption on social and economic development. This study uses a quantitative approach with a pretest-posttest design, where data is collected through questionnaires given to participants before and after participating in anti-corruption education. The results of the study showed a significant increase in the level of understanding of the younger generation about the concept and dangers of corruption after participating in the education. Before attending the education, most of the participants had a limited understanding of the impact of corruption, but after the education, they showed a deeper and more critical understanding of the issue. This research is expected to contribute to efforts to increase public awareness about the importance of eradicating corruption, especially through education based on the values of honesty and integrity.